The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/jbio.201400104
|View full text |Cite
|
Sign up to set email alerts
|

Application of circularly polarized light for non‐invasive diagnosis of cancerous tissues and turbid tissue‐like scattering media

Abstract: Polarization-based optical techniques have become increasingly popular in the field of biomedical diagnosis. In the current report we exploit the directional awareness of circularly and/or elliptically polarized light backscattered from turbid tissue-like scattering media. We apply circularly and elliptically polarized laser light which illuminates the samples of interest, and a standard optical polarimeter is used to observe the polarization state of light backscattered a few millimeters away from the point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
158
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(174 citation statements)
references
References 17 publications
4
158
1
Order By: Relevance
“…For many tissues, µ t is much greater than (µ a + µ s ′). Therefore, in certain situations, it is impossible to detect pure ballistic photons (photons that do not experience scattering), but forward scattered photons retain their initial polarization and can be used for imaging purpose [5,9,10,[71][72][73][74][75][76][77]. There was experimentally demonstrated that laser radiation retains linear polarization on the level of P L ≤ 0.1 within 2.5l tr .…”
Section: Multiple Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…For many tissues, µ t is much greater than (µ a + µ s ′). Therefore, in certain situations, it is impossible to detect pure ballistic photons (photons that do not experience scattering), but forward scattered photons retain their initial polarization and can be used for imaging purpose [5,9,10,[71][72][73][74][75][76][77]. There was experimentally demonstrated that laser radiation retains linear polarization on the level of P L ≤ 0.1 within 2.5l tr .…”
Section: Multiple Scatteringmentioning
confidence: 99%
“…The polarization imaging is a prospective direction in tissue optics [5,9,10,[71][72][73][74][75][76][77]. The registration of two-dimensional polarization patterns for the backscattering of a polarized incident narrow laser beam is the basis for this technique.…”
Section: Multiple Scatteringmentioning
confidence: 99%
“…Polarization imaging is regarded as a promising technique for probing the microstructures, especially the anisotropic fibrous components of complex scattering samples [11,12]. Among the available polarimetric techniques, Mueller matrix imaging has many distinctive advantages, such as providing label-free and comprehensive descriptions on the properties of tissues, cells, and other biological specimens [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Polarization imaging techniques are recognized as potentially powerful methods to detect the pathological changes of biological tissues [1][2][3][4]. In the past decades many attempts have been made for clinical diagnosis applications using simple polarization parameters such as the degree of polarization (DOP) [5,6] and difference polarization (DP) [7].…”
Section: Introductionmentioning
confidence: 99%